Geometric Abstraction Stages at Art Education - Bayraktar, Alkan (Elsevier BV, 2012)
AbstractAbstraction is the remodelling of nature objects, and then it is completely alienation from nature objects’ styles. Abstract art is seen as the maximum point of this abstraction (Kalkan, 2006). Abstract painting may be created with geometrical styles by the help of some technical means as it is being done in many forms. Abstract art know-how starts with the problem of after 16 age young generation's rehashing request for many portraits existing in nature. Because, individual may bring a new perception and perspective to them by breaking the simplicity on some structural events’ forms that he has seen in nature during his education until that time. During the transfer and implementation of the stages at very important abstraction process to individual, educators take on the task of guiding. So, educators must know the abstraction process stages in detail. Therefore in litterateur, there has been no complementary and summative study that will direct educators and guide them about related subject. A study that aims to fill the deficiency related to the area will be done and the aim of this research is to analyse geometric abstraction stages at art education. Research was planned through qualitative research approach and relevant literature were evaluated and summarized by using document analysis.
Keywords: Art Education; Abstract Painting; Geometric Abstraction Stages; 4. Education